The KOF Globalisation Index - Revisited - Savina Gygli; Florian Haelg; Niklas Potrafke; Jan-Egbert Sturm (Center for Economic Studies and ifo Institute (CESifo), 2018)
We introduce the revised version of the KOF Globalisation Index, a composite index measuring globalization for every country in the world along the economic, social and political dimension. The original index was introduced by Dreher (2006) and updated in Dreher et al. (2008). This second revision of the index distinguishes between de facto and de jure measures along the different dimensions of globalization. We also disentangle trade and financial globalization within the economic dimension of globalization and use time-varying weighting of the variables. The new index is based on 43 instead of 23 variables in the previous version. Following Dreher (2006), we use the new index to examine the effect of globalization on economic growth. The results suggest that de facto and de jure globalization influence economic growth differently. Future research should use the new KOF Globalisation Index to re-examine other important consequences of globalization and why globalization was proceeding rapidly in some countries, such as South Korea, but less so in others.
Keywords: F15; F36; F43; F53; F60; F62; O19; O24; O57; Y10; 330; globalization; composite indicators